2017
DOI: 10.1038/ncomms14895
|View full text |Cite
|
Sign up to set email alerts
|

Rapid population decline in migratory shorebirds relying on Yellow Sea tidal mudflats as stopover sites

Abstract: Migratory animals are threatened by human-induced global change. However, little is known about how stopover habitat, essential for refuelling during migration, affects the population dynamics of migratory species. Using 20 years of continent-wide citizen science data, we assess population trends of ten shorebird taxa that refuel on Yellow Sea tidal mudflats, a threatened ecosystem that has shrunk by >65% in recent decades. Seven of the taxa declined at rates of up to 8% per year. Taxa with the greatest relian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
348
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(394 citation statements)
references
References 45 publications
15
348
4
2
Order By: Relevance
“…Along the EAAF, habitat deterioration and loss of major stopover sites, e.g. within the Yellow Sea, occur at an alarming rate (Murray et al 2014(Murray et al , 2015, and are demonstrated to correlate highly with the shorebirds' population declines (Studds et al 2017). Large birds in this case may be thought more vulnerable for such adverse effects, given their incapacity for a fast migration.…”
Section: Discussionmentioning
confidence: 99%
“…Along the EAAF, habitat deterioration and loss of major stopover sites, e.g. within the Yellow Sea, occur at an alarming rate (Murray et al 2014(Murray et al , 2015, and are demonstrated to correlate highly with the shorebirds' population declines (Studds et al 2017). Large birds in this case may be thought more vulnerable for such adverse effects, given their incapacity for a fast migration.…”
Section: Discussionmentioning
confidence: 99%
“…The population status of and threats to waterbirds in China is increasingly concerned due to China's importance for waterbird conservation along the flyways. For example, in recent years, many studies have indicated that loss of wetlands along China's coast is the most serious threat to migratory shorebirds along the flyway, causing dramatic declines in many populations Piersma et al 2016;Studds et al 2017). Currently, only a few waterbird species (e.g., some cranes, storks, and spoonbills, ibises, geese) have been well studied in terms of their population dynamics Zhang et al 2010;Luo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although their movements are unidirectional and relatively linear, they must be able to access adequate and complementary resources from the different areas of their "home range" in a reasonably energetically efficient way with minimal risky or costly gap crossings. Habitat fragmentation has an impact when barriers are erected along their migratory path or important stopover nodes are lost so they cannot reach their seasonal destination (Simpson et al, 2016;Studds et al, 2017). Thus, long-distance migrants are perhaps less likely to experience impeded gene flow because of their high mobility, and their movement restrictions are most likely to fall within the category of impeded resource access, albeit at a much grander scale than that observed for more-sedentary species.…”
Section: Fine-scale Mechanism-limited Resource Accessmentioning
confidence: 99%